2018
DOI: 10.1177/0194599818766320
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Pathogenic Structures Affixed to the Tympanic Membrane during Chronic Otitis Media

Abstract: Objective To characterize otitis media-associated structures affixed to the mucosal surface of the tympanic membrane (TM) in vivo and in surgically recovered in vitro samples. Study Design Prospective case series without comparison. Setting Outpatient surgical care center. Subjects and Methods Forty pediatric subjects scheduled for tympanostomy tube placement surgery were imaged intraoperatively under general anesthesia. Postmyringotomy, a portable optical coherence tomography (OCT) imaging system assessed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 61 publications
3
26
0
1
Order By: Relevance
“…In general, biofilms tend to exhibit a stronger (brighter) OCT signal than the TM, and frequently appear as a distinct, additional, and layered structure affixed to the TM, based on OCT A-scan profiles ( Guder et al 2015 ; Nguyen et al 2010 , 2012 ). Nonetheless, in this study, the presence of MEEs and/or biofilm has not been biologically confirmed via invasive sampling as in the study from Monroy et al (2018) . Subjects in this study were outpatients who did not undergo any surgical procedure at the time of the visit.…”
Section: Methodsmentioning
confidence: 61%
“…In general, biofilms tend to exhibit a stronger (brighter) OCT signal than the TM, and frequently appear as a distinct, additional, and layered structure affixed to the TM, based on OCT A-scan profiles ( Guder et al 2015 ; Nguyen et al 2010 , 2012 ). Nonetheless, in this study, the presence of MEEs and/or biofilm has not been biologically confirmed via invasive sampling as in the study from Monroy et al (2018) . Subjects in this study were outpatients who did not undergo any surgical procedure at the time of the visit.…”
Section: Methodsmentioning
confidence: 61%
“…Our group has previously used high-end 800-nm OCT systems for TM imaging, which has led to several new findings. [17][18][19]44 Here, we have shown representative skin images to test the applicability and feasibility of our system. The presented system, however, was not fully optimized for TM imaging, and efforts are being made to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Several successful middle ear-related OCT studies have been conducted, and have shown the exceptional capabilities of OCT in aiding the identification of sub-surface tissue differentiation and localization of critical structures [21]- [23]. Moreover, the thickness of the TM membrane can be visualized and quantitatively analyzed using OCT to delineate the relevant morphological structures [24]- [26]. Pre-identification of these morphological changes in vivo at an early stage not only offers a value from a research point of view, but may also be beneficial to understanding the changes that occur during the process of infection.…”
Section: Introductionmentioning
confidence: 99%